Implementasi Penanganan Stunting di Desa Sawaran Lor Kecamatan Klakah Kabupaten Lumajang - Sholihah, Millatus; Yuraida, Nizma (Majalah Ilmiah DIAN ILMU, 2023)
The condition of failure to thrive in toddlers which causes their heightgrowth to be shorter than their age standard is called Stunting. Stunting can beprevented with various alternatives, one of which is the policy of Law Number36 of 2009 concerning health, which provides the basis and guidance for thegovernment in managing the national health system, including efforts toprevent and reduce stunting rates. However, the prevalence of stunting is stillincreasing, one of which is in Klakah District, Lumajang Regency. Thisresearch aims to evaluate the implementation of stunting management inKlakah District, Lumajang Regency. In this research, the method used is adescriptive qualitative paradigm. The technique for determining informantsuses purposive sampling where the researcher is the key informant. Theresearch location is Sawaran Lor Village, Klakah District, Lumajang Regency.The results of the research show that the handling of stunting in Sawaran LorVillage, Klakah District, Lumajang Regency has been implemented well, buthas not yet run optimally. One of them is the indicator of socialization to thecommunity, there are still many pregnant women and those with toddlers whodo not understand stunting. Based on this, we should carry out regular outreachto the community so that the implementation of handling stunting in SawaranLor Village, Klakah District, Lumajang Regency can run optimally.